2019
DOI: 10.1093/intimm/dxz017
|View full text |Cite
|
Sign up to set email alerts
|

Gp49B is a pathogenic marker for auto-antibody-producing plasma cells in lupus-prone BXSB/Yaamice

Abstract: Immune homeostasis is critically regulated by the balance between activating and inhibitory receptors expressed on various immune cells such as T and B lymphocytes, and myeloid cells. The inhibitory receptors play a fundamental role in the immune checkpoint pathway, thus maintaining peripheral tolerance. We recently found that expression of leukocyte immunoglobulin-like receptor (LILR)B4, an inhibitory member of the human LILR family, is augmented in auto-antibody-producing plasmablasts/plasma cells of systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…For antibody treatment, the B6 mice were inoculated intravenously at a low dose of 5 × 10 5 LLC-Luc2 cells or 5 × 10 4 B16F10 cells. At 3 days post-tumor inoculation, mice were treated with anti-PD-1 (RPM1-14, Bio X Cell; 200 μg/mouse), anti-gp49 (H1.1-Amenian hamster IgG from hybridoma cells 26 or H1.1-mIgG1, 200 μg/mouse), or isotype matched control antibody (2A3 (Bio X cell), HTK888 (Biolegend) or MOPC-21 (Bio X Cell); 200 μg/mouse) by intraperitoneal injection six times at 3-day intervals. LLC-Luc2 tumor-bearing mice with antibody treatment were imaged using the IVIS Spectrum In Vivo Imaging System (Perkin Elmer) at three weeks after tumor inoculation, and sacrificed at five weeks after tumor injection for detection of tumor metastases in lung and liver by H&E staining.…”
Section: Methodsmentioning
confidence: 99%
“…For antibody treatment, the B6 mice were inoculated intravenously at a low dose of 5 × 10 5 LLC-Luc2 cells or 5 × 10 4 B16F10 cells. At 3 days post-tumor inoculation, mice were treated with anti-PD-1 (RPM1-14, Bio X Cell; 200 μg/mouse), anti-gp49 (H1.1-Amenian hamster IgG from hybridoma cells 26 or H1.1-mIgG1, 200 μg/mouse), or isotype matched control antibody (2A3 (Bio X cell), HTK888 (Biolegend) or MOPC-21 (Bio X Cell); 200 μg/mouse) by intraperitoneal injection six times at 3-day intervals. LLC-Luc2 tumor-bearing mice with antibody treatment were imaged using the IVIS Spectrum In Vivo Imaging System (Perkin Elmer) at three weeks after tumor inoculation, and sacrificed at five weeks after tumor injection for detection of tumor metastases in lung and liver by H&E staining.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we further demonstrated that CRD enhanced the expression of LILRB4 in vivo in healthy mammary glands and mammary tumors. LILRB4 is an inhibitory receptor that plays a key role in immune checkpoint pathways ( 63 ). Regarding signals transmitted by LILRs, the cytoplasmic immunoreceptor tyrosine-based inhibitory motifs (ITIMs) and immunoreceptor tyrosine-based activating motifs (ITAMs) are of great significance ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pinpointing autoantibody-producing plasmablasts (PBs) and plasma cells (PCs) by finding effective target molecules is essential for downregulating pathogenic plasma cell activity. It was found that PBs and PCs from untreated SLE patients would have high LILRB4 expression, and that the level of LILRB4 expression was positively correlated with the production of anti-double-stranded DNA IgG in serum [19,79]. Therefore, utilizing the highly expressed LILRB4 molecule to recognize pathogenic PBs/PCs and target pathogenic PBs/PCs could provide a new avenue for effective treatment of SLE.…”
Section: Lilrb4 and Autoimmune Tolerancementioning
confidence: 99%